Acute injection‐related infections requiring hospitalisation among people who inject drugs: Clinical features, microbiology and management. (22nd August 2022) - Langham, Freya J.; Curtis, Stephanie J.; Tang, Mei Jie; Jomon, Bismi; Doyle, Joseph S.; Vujovic, Olga; Stewardson, Andrew J.
Abstract: Introduction: People who inject drugs are at risk of hospitalisation with injection‐related infections (IRI). We audited the clinical features, microbiology and management of IRI at a tertiary service in Melbourne to describe the burden and identify quality improvement opportunities. Methods: We performed retrospective review of IRI admissions from January 2017 to April 2019. We extracted admissions where ICD‐10 codes or triage text suggested injecting drug use, and the diagnosis suggested IRI. We reviewed these for eligibility and extracted data using a standardised form. We performed mixed‐effects logistic regression to determine predictors of unplanned discharge. Results: From 574 extracted candidate admissions, 226 were eligible, representing 178 patients. Median age was 41 years (interquartile range 36–47), 66% (117/178) male and 49% (111/226) had unstable housing. Over 50% (96/178) had a psychiatric diagnosis and 35% (62/178) were on opioid agonist therapy (OAT) on admission. Skin and soft tissue infection was the most common IRI (119/205, 58%), followed by bacteraemia (36/205, 18%) and endocarditis (26/205, 13%). Management included addictions review (143/226, 63%), blood‐borne virus screening (115/226, 51%), surgery (77/226, 34%) and OAT commencement (68/226, 30%). Aggression events (54/226, 15%) and unplanned discharge (69/226, 30%) complicated some admissions. Opioid use without OAT was associated with almost 3‐fold increased odds of unplanned discharge compared to no opioid use (odds ratio 2.90, 95% confidence interval 1.23, 6.85, p = 0.015). Discussion and Conclusion: Comorbidities associated with IRI may be amenable to opportunistic intervention during hospitalisation. Further research is needed to develop optimal models of care for this vulnerable patient group.